2017
DOI: 10.1021/acs.jafc.6b04816
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Solid Anaerobic Digestate Soil Amendments for Effects on Soil Quality and Biosolarization Efficacy

Abstract: Anaerobic digestion is an organic waste bioconversion process that produces biofuel and digestates. Digestates have potential to be applied as soil amendment to improve properties for crop production including phytonutrient content and pest load. Our objective was to assess the impact of solid anaerobic digestates on weed seed inactivation and soil quality upon soil biosolarization (a pest control technique that combines solar heating and amendment-induced microbial activity). Two solid digestates from thermop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…In addition to these specific impacts, other studies also observed that organic amendments followed by solarization led to higher values of total N, total P, several enzyme activities, microbial biomass C, potentially mineralizable N, water‐soluble organic C and microbial functional diversity when compared with non‐amended soils . Biosolarization studies using thermophilic and mesophilic digestates showed a significant decrease in EC after solarization . In this study, the increase in EC may suggest a need for irrigation after SBS application to avoid negative effects on crops if EC levels are not naturally recovered after SBS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to these specific impacts, other studies also observed that organic amendments followed by solarization led to higher values of total N, total P, several enzyme activities, microbial biomass C, potentially mineralizable N, water‐soluble organic C and microbial functional diversity when compared with non‐amended soils . Biosolarization studies using thermophilic and mesophilic digestates showed a significant decrease in EC after solarization . In this study, the increase in EC may suggest a need for irrigation after SBS application to avoid negative effects on crops if EC levels are not naturally recovered after SBS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the increase in EC may suggest a need for irrigation after SBS application to avoid negative effects on crops if EC levels are not naturally recovered after SBS. SBS also decreased the NO 3 ‐ concentration and this effect was also observed in prior studies . This may be a negative outcome as NO 3 ‐ is the preferred form of nitrogen for plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the same treatment using 1·5 wt% mesophilic digestate did not significantly increase B. nigra mortality compared to the control treatments (Fernandez‐Bayo et al . ). It is possible that differences in performance were due in part to compositional differences in the amended substrate and micro‐organisms involved in the biotransformation of substrates to biopesticidal compounds (Fernandez‐Bayo et al .…”
Section: Introductionmentioning
confidence: 97%